A rare case of short stature – pituitary stalk transection syndrome - Dr. Lakshmipriya Chadalawada; Dr. Rachana Nimmagadda; Dr. Hemanth Vupputuri; Dr. Vijayalakshmi Bhimireddy (Pediatric Review: International Journal of Pediatric Research, 2019)
Short stature due to Growth hormone deficiency could be due to multiple etiologies. One such rare cause is the Pituitary stalk transection syndrome which is characterized by a triad of thin or absent pituitary stalk, aplasia or hypoplasia of the anterior pituitary and absent or ectopic posterior pituitary seen on magnetic resonance imaging (MRI). The early identification of growth hormone deficiency through growth hormone stimulation tests, evaluation of the hypothalamic-pituitary anatomy by performing MRI brain and the early initiation of growth hormone replacement therapy may salvage the child from pathological short stature.